Mucoadhesive films based on gellan gum/pectin blends as potential platform for buccal drug delivery. (7th February 2020) - Prezotti, Fabíola Garavello; Siedle, Izabel; Boni, Fernanda Isadora; Chorilli, Marlus; Müller, Ingrid; Cury, Beatriz Stringhetti Ferreira
Abstract: Films of gellan gum:pectin blends were prepared by solvent casting method. Gellan gum:pectin mass ratios were varied (4:1; 1:1; 1:4) at different concentrations (3% or 4%) and glycerol was used as plasticizer (1 or 2%). The films were thin (18–30 µm), translucent, flexible, and homogeneous. The surface pH was suitable for buccal application. All films reached high mechanical resistance and the mucoadhesive ability of them was evidenced. High ratio of gellan gum improved the mechanical resistance and the mucoadhesion of the films as well as the control of drug release rates. The films did not disintegrate in simulate saliva up to 24 h and curcumin release could be sustained up to 12 h. The set of data evidence that the films designed in this work represent a potential platform for buccal drug delivery. Graphical Abstract: